The handbook of global companies - Mikler, John. (Chichester, West Sussex, UK : Wiley-Blackwell, 2013)
The Handbook of Global Companies brings together original research addressing the latest theories and empirical analysis surrounding the role of global companies in local, national, and international governance. Offers new insights into the role of global companies in relation to policy and governance at local, national, and international levels. Brings together newly-commissioned research by a global team of established and up-and-coming scholars from the fields of international relations, political science, public policy, and beyond. Considers the environme.
pt. 1. Locating global companies -- pt. 2. Global companies and power -- pt. 3. Global companies and the state -- pt. 4. Global companies and international organizations -- pt. 5. Global companies and society -- pt. 6. The exercise and limitations of private global governance.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: International business enterprises -- Political aspects; Business and politics; International relations; International business enterprises -- Political aspects; POLITICAL SCIENCE -- Political Process -- Political Advocacy; Business and politics; International business enterprises -- Political aspects; International relations; Multinationales Unternehmen; Internationalisierung; Einflussnahme; Politik; Electronic books